2004
DOI: 10.1099/vir.0.80347-0
|View full text |Cite
|
Sign up to set email alerts
|

Replication of varicella-zoster virus is influenced by the levels of JNK/SAPK and p38/MAPK activation

Abstract: Stimulation of the Jun NH 2 -terminal kinase/stress-activated protein kinase (JNK/SAPK) and the p38 mitogen-activated protein kinase (p38/MAPK) is part of the stress-related signal transduction pathways conveying signals from the cell surface into the nucleus in order to initiate programmes of gene expression. Here, it was shown that infection by varicella-zoster virus (VZV) caused a 34-fold increase in activation of JNK/SAPK in the early phase of infection and a 2-fold increase in activation of p38/MAPK in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 51 publications
2
83
1
Order By: Relevance
“…An increasing amount of information has demonstrated that many viruses activate the p38 MAPK pathway to augment their efficient replication (51)(52)(53)(54)(55). To this end, although in our earlier study we have demonstrated that p38 MAPK activation is beneficial for ARV replication (31), its precise role in regulating ARV entry and replication remains elusive so far.…”
Section: Discussionmentioning
confidence: 90%
“…An increasing amount of information has demonstrated that many viruses activate the p38 MAPK pathway to augment their efficient replication (51)(52)(53)(54)(55). To this end, although in our earlier study we have demonstrated that p38 MAPK activation is beneficial for ARV replication (31), its precise role in regulating ARV entry and replication remains elusive so far.…”
Section: Discussionmentioning
confidence: 90%
“…ERK1/2 is known to be activated through the Ras/Raf/MEK pathway in response to various growth factors and to play a central role in cell proliferation (43). The replication of varicella zoster virus is positively regulated by activated p38, and the activation of this stress pathway activates cellular transcription factors, but prevents the activation of cellular defense mechanisms (44). MAPKs (including p38) have been shown to play important roles in the immune response from Th1/Th2 differentiation (14,19,45) to the host's defense against various pathogens, including viruses (19,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…There is also an increasing body of literature showing that JNK activation follows bacterial, fungal, prion, parasitic, or viral infections. Under these circumstances, JNK activation may influence important cellular consequences, such as alterations in gene expression (1,53,59,162,167,176,199,294,325,326,346), cell death (58,89,137,139,169,193,243,293), viral replication, persistent infection or progeny release (215,224,251,260), or altered cellular proliferation (178). The exact mechanism of JNK activation under each of these circumstances remains to be elucidated fully, although there may be involvement of Toll-like receptors, direct pathway modulation through interaction with upstream protein regulators, or the activation following an ER stress response (79,87,110,124,143,191,253,261,279,294,312).…”
Section: Fig 1 Overview Of the Jnk Pathway (A)mentioning
confidence: 99%